Effects of a Home-Based Telephone-Supported Physical Activity Program for Older Adult Veterans With Chronic Low Back Pain. Issue 5 (16th April 2018) - Goode, Adam P; Taylor, Shannon Stark; Hastings, Susan N; Stanwyck, Catherine; Coffman, Cynthia J; Allen, Kelli D
Abstract: Background: Chronic low back pain (CLBP) is highly prevalent in older adults, leading to functional decline. Objective: The objective of this study was to evaluate physical activity (PA) only and PA plus cognitive-behavioral therapy for pain (CBT-P) among older adult veterans with CLBP. Design: This study was a pilot randomized trial comparing a 12-week telephone–supported PA-only intervention group (PA group) or PA plus CBT-P intervention group (PA + CBT-P group) and a wait-list control group (WL group). Setting: The study setting was the Durham Veterans Affairs Health Care System. Participants: The study participants were 60 older adults with CLBP. Interventions: The PA intervention included stretching, strengthening, and aerobic activities; CBT-P covered activity pacing, relaxation techniques, and cognitive restructuring. Measurements: Feasibility measures included enrollment and completion metrics; acceptability was measured by completed phone calls. Primary outcomes included the Timed "Up & Go" Test and the PROMIS Health Assessment Questionnaire. Generalized linear mixed models were used to estimate changes within and between groups. Effect sizes were calculated with the Cohen d . Adverse effects were measured by self-report. Results: The mean participant age was 70.3 years; 53% were not white, and 93% were men. Eighty-three percent of participants completed the study, and the mean number of completed phone calls was 10 (of 13). Compared with the results for the WL group, small to medium treatment effects were found for the intervention groups in the Timed "Up & Go" Test (PA group: −2.94 [95% CI = −6.24 to 0.35], effect size = −0.28; PA + CBT-P group: –3.26 [95% CI = −6.69 to 0.18], effect size = −0.31) and the PROMIS Health Assessment Questionnaire (PA group: −6.11 [95% CI = −12.85 to 0.64], effect size = −0.64; PA + CBT-P group: –4.10 [95% CI = –11.69 to 3.48], effect size = −0.43). Small treatment effects favored PA over PA + CBT-P. No adverse effects were noted. Limitations: This was a pilot study, and a larger study is needed to verify the results. Conclusions: This pilot trial demonstrated that home-based telephone-supported PA interventions were feasible, acceptable, and safe for older adult veterans. The results provide support for a larger trial investigating these interventions.